The configuration of the Andean landscape in the poetic discourse of Puno vanguardism - Quispe Mendivil, Yoselin (2021)
The objective of this research work is to compare the similarities and differences with respect to the configuration of the Andean landscape in the poem “balsas matinales”, in Ande (1926), by Alejandro Peralta versus “Yaraví Titicaca”, in Altipampa (1933) by Emilio Vásquez. This study postulates that in Peralta's poetic discourse it vindicates in a more marked way the importance of the daily activities of the andean man such as fishing, pastoralism, agriculture, cattle ranching, andeanism and andean patronal saint festivals. On the other hand, in Vázquez's poetic discourse, the pampa and lago categories are used to a greater extent to indicate the influence of these landscapes on the subjectivity of the Andean man. To carry out the study are used the theoretical frameworks of Rhetoric and Comparative literature and, therefore, are followed the guidelines of Arduini (2000) and Steiner (1978-1992), respectively.